New low viscous cholinium-based magnetic ionic liquids. (10th February 2016) - Rosatella, Andreia A.; Siopa, Filipa; Frade, Raquel F. M.; Afonso, Carlos A. M.
Abstract : This study describes the synthesis of cholinium-based magnetic ionic liquids that are liquid at room temperature and have low toxicity to human cells. Abstract : Magnetic ionic liquids (MILs) are a type of ionic liquids (ILs) that have paramagnetic metal based anions, and thus they can respond to an external magnetic field. Owing to the high propensity of these anions to crystallize, there are only few reported MILs that are liquid at room temperature. This study describes a new family of cholinium based ILs containing two and three ethanol side chains, that are liquid at room temperature, even in combination with paramagnetic anions. In addition, these new family of ILs are prone to the generation of low toxicities on human cell lines.